Boron‐Mediated Grain Boundary Engineering Enables Simultaneous Improvement of Thermoelectric and Mechanical Properties in N‐Type Bi2Te3. Issue 42 (19th September 2021) - Zhang, Chaohua; Geng, Xingjin; Chen, Bin; Li, Junqin; Meledin, Alexander; Hu, Lipeng; Liu, Fusheng; Shi, Jigui; Mayer, Joachim; Wuttig, Matthias; Cojocaru‐Mirédin, Oana; Yu, Yuan
Abstract: Powder metallurgy introduces small structures of high‐density grain boundaries into Bi2 Te3 ‐based alloys, which promises to enhance their mechanical and thermoelectric performance. However, due to the strong donor‐like effect induced by the increased surface, Te vacancies form in the powder‐metallurgy process. Hence, the as‐sintered n‐type Bi2 Te3 ‐based alloys show a lower figure of merit ( ZT ) value than their p‐type counterparts and the commercial zone‐melted (ZM) ingots. Here, boron is added to one‐step‐sintered n‐type Bi2 Te3 ‐based alloys to inhibit grain growth and to suppress the donor‐like effect, simultaneously improving the mechanical and thermoelectric (TE) performance. Due to the alleviated donor‐like effect and the carrier mobility maintained in our n‐type Bi2 Te2.7 Se0.3 alloys upon the addition of boron, the maximum and average ZT values within 298–473 K can be enhanced to 1.03 and 0.91, respectively, which are even slightly higher than that of n‐type ZM ingots. Moreover, the addition of boron greatly improves the mechanical strength such as Vickers hardness and compressive strength due to the synergetic effects of Hall‐Petch grain‐boundary strengthening and boron dispersion strengthening. This facile and cost‐effective grain boundary engineering by adding boron facilitates the practical application of Bi2 Te3 ‐based alloys and can also be popularized in other thermoelectric materials. Abstract : A facile strategy of adding boron is proposed to induce the grain refinement but simultaneously suppress the donor‐like effect in one‐step sintered n‐type Bi2 Te3 ‐based alloys, which results in grain‐boundary strengthening and pinning effect for robust mechanical strength and optimization of carrier density and mobility for enhanced thermoelectric performance.